2008
DOI: 10.1007/s11055-008-9064-8
|View full text |Cite
|
Sign up to set email alerts
|

The question of the fusion of neuron processes

Abstract: The authors, whilst accepting the neuron theory, present data indicating the possibility that neuronal syncytia exist when myelin-coated ring-like structures form in the dendritic field, in nerve arcades close to neuron bodies, and on formation of thick, straight anastomoses between neuron bodies. Studies using computerized time-lapse videomicroscopy in cultures of isolated neurons demonstrated the mechanism by which these structures form. This report provides the first evidence of the time parameters of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Work in cell culture has revealed that only the transmembrane isoforms A and B were capable of mediating cellcell fusion 29 , and only isoform A has been found to rescue morphological defects in vivo 34 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Work in cell culture has revealed that only the transmembrane isoforms A and B were capable of mediating cellcell fusion 29 , and only isoform A has been found to rescue morphological defects in vivo 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It has a crucial role in fusing a variety of C. elegans cells during normal development to generate syncytia 25 . This molecule is also able to mediate membrane fusion in vitro in other cellular contexts [26][27][28][29][30][31] . EFF-1 must be inserted into both membranes to mediate fusion; current models suggest that its mechanism of action involves the formation of trimers in trans across apposing membranes 28,31 .…”
mentioning
confidence: 99%
See 3 more Smart Citations